1987
DOI: 10.1111/j.1748-1716.1987.tb08204.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of prostaglandin synthesis inhibition on motility of the sheep ureter

Abstract: To determine the effect of prostaglandin-synthesis inhibition on ureteral motility, isolated rings of sheep ureters were suspended for recording isometric tension in organ baths filled with Krebs-Henseleit solution. The non-steroidal anti-inflammatory drugs (NSAIDs) indomethacin and diclofenac sodium (10(-5) M) inhibited rhythmic ureteral motility by reducing frequency, amplitude and finally stopping contractions. Prostaglandin F2 alpha, 6-keto-prostaglandin F1 alpha and thromboxane B2 were determined by radio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 13 publications
1
13
0
Order By: Relevance
“…The present study shows that the human upper urinary tract, the renal pelvis and the ureter are able to synthesise eicosanoids, as has been found in the bladder of man (Abrams et al, 1979;Jeremy et al, 1987) and of rabbit (Brown et al, 1980). These results give credance to the study of Al-Ugaily et al (1986), who suggested that the large number of lipophilic granules seen in the vicinity of smooth muscle cells on electron microscopy could serve as prostaglandin precursors and reinforce the results of Thulesius (1987), who found eicosanoid release from sheep ureter into an organ bath.…”
Section: Discussionsupporting
confidence: 85%
“…The present study shows that the human upper urinary tract, the renal pelvis and the ureter are able to synthesise eicosanoids, as has been found in the bladder of man (Abrams et al, 1979;Jeremy et al, 1987) and of rabbit (Brown et al, 1980). These results give credance to the study of Al-Ugaily et al (1986), who suggested that the large number of lipophilic granules seen in the vicinity of smooth muscle cells on electron microscopy could serve as prostaglandin precursors and reinforce the results of Thulesius (1987), who found eicosanoid release from sheep ureter into an organ bath.…”
Section: Discussionsupporting
confidence: 85%
“…indomethacin, produce a profound inhibitory effect on spontaneous or evoked motility of isolated pyeloureteral smooth muscle from various species (Thulesius & Angelo-Khattar 1985;Lundstam et al, 1985;Thulesius et al, 1986;1987;Cole et al, 1988;Kimoto & Constantinou, 1991): the general conclusion emerging from these studies is that prostanoid generation is an important step for the local regulation of pyeloureteral motility. In some studies, a complete suppression of pyeloureteral motility by COX inhibitors has been reported (Lundstam et al, 1984;Thulesius & Angelo-Khattar 1985;Thulesius et al, 1987;Cole et al, 1988): this may suggest that prostanoid generation is mandatory for the maintenance/activation of ureteral peristalsis. The evidence from this approach is, however, strictly limited by the selectivity and specificity of the pharmacological tools employed.…”
Section: Introductionmentioning
confidence: 97%
“…As reference we had to rely on sheep gallbladder strips which apparently qualita tively responded to cholinergic stimulation like human specimens. The selection of ovine gallbladders was a com promise since these specimens are always readily avail able from freshly slaughtered sheep and we have previous extense experience with smooth muscle preparations from sheep [9] which basically responded in a similar way to human specimens [10]. In our study we chose carbachol as a stimulant of contractility since we found that the nat urally occurring agonist cholecystokinin in a series of 12 experiments only resulted in a 59% efficacy (maximal response) as compared to carbachol (results not shown).…”
Section: Discussionmentioning
confidence: 99%